Analysis of factors influencing doctors' awareness of clinical guidelines for heart failure treatment - N. B. Perepech; A. V. Tregubov; I. E. Mikhailova (Российский кардиологический журнал, 2024)
Aim. To find out the relationship between the awareness level of clinical guidelines on heart failure (HF) with reduced ejection fraction and a number of professional characteristics (specialty, work experience, self-assessment of awareness level, attitude towards the use of guidelines, the main way of document study). To improve the efficiency and development of the postgraduate education system, the factors that influence doctors' awareness of guidelines should be determined.Material and methods. The study included the results of an anonymous survey of 207 doctors (155 cardiologists, 44 therapists, 8 doctors of other specialties). To assess the significance of differences, Student's t-test, c2-test and Fisher's exact test were used.Results. The mean number of correct answers to the questionnaire among cardiologists was significantly higher than among general practitioners (p<0,001). In the group of physicians with less than 5 years of work experience, there was a large variability in the mean number of correct answers — 6,2±4,0. Physicians with 6-10 years and 11-20 years of experience in their specialty were more likely to choose the correct answers than doctors with more than 20 years of experience. Professionals who considered themselves "fully informed" on clinical guidelines gave fewer correct answers than doctors who had less high self-rating (p<0,001). The proportion of correct answers in the subgroup of doctors who consider guidelines to be mandatory was greater than in the subgroups of doctors who hold a different opinion (p<0,05). The best results were shown by physicians who indicated direct text-oriented way as preferred for studying guidelines (p<0,001).Conclusion. The awareness level of clinical guidelines on the treatment of HF by cardiologists should be considered insufficient, and by therapists — extremely low. Doctors are not sufficiently informed about the need to comply with clinical guidelines. When planning training, the specialty and work experience of the doctor should be taken into account. Unjustifiably high self-rating of knowledge interferes with professional development. The best way of self-education should be considered direct study of the text of clinical guidelines.